Xinyue Capsule in patients with stable coronary artery disease after percutaneous coronary intervention: a multicenter, randomized, placebo-controlled trial. (August 2020) - Guo, Ming; Wang, Peili; Du, Jianpeng; Fu, Changgeng; Yang, Qiaoning; Gao, Zhuye; Zhu, Mingjun; Lv, Shuzheng; Deng, Yue; Li, Tianchang; Shi, Dazhuo; Working Group, for the XY
Graphical abstract: Abstract: Background: Xinyue capsule, a patented Chinese herbal medicine, has been used to manage coronary artery disease (CAD) for over a decade in China, but whether it can further reduce risk of cardiovascular events beyond conventional treatment is unknown. Methods: In this multicenter, randomized, placebo-controlled trial, we randomly assigned patients with stable CAD who underwent percutaneous coronary intervention (PCI) within the preceding 3-12 months to receive Xinyue capsule (100 mg panax quinquefolius saponins, three times a day) or placebo for 24 weeks in addition to conventional treatment. The primary endpoint was a composite that included cardiac death, nonfatal myocardial infarction and urgent revascularization with either PCI or coronary artery bypass grafting. The secondary composite endpoints included stroke, re-hospitalization due to acute coronary syndrome (ACS), pulmonary embolism, peripheral vascular events and all-cause mortality. Quality of life was assessed using a 36-item Short-Form Health Survey (SF-36). Results: A total of 1054 participants were included in the analyses. The median follow up was 1 year. The primary endpoint events occurred in 16 patients (3.02%) in the Xinyue group and 34 patients (6.49%) in the placebo group (hazard ratio [HR] 0.455, 95% confidence interval [CI] 0.25 to 0.825; P = 0.009). Secondary end-point events occurred in 5.47% of patients in the Xinyue group and 10.31% in the placebo group (HR 0.515, 95% CI 0.328 to 0.809; P = 0.004). SF-36 subscale scores at 12 months were significantly higher in the Xinyue group than placebo group for general health (P = 0.048) and vitality (P = 0.008). Conclusions: In patients with stable CAD after PCI within the preceding 3 to 12 months, Xinyue capsule added on conventional treatment reduced the incidence of primary composite endpoint (cardiac death, nonfatal myocardial infarction and urgent revascularization).